Investigating the effects of strategic positioning for development of modern banking services - Vahid Anvar Keivi; Saba Kamali; Ebrahim Shahrami Manesh; Samira Najafi; Ali Arfaeean; Seyed Shahab Mousavi (Management Science Letters)
During the past few years, there have been tremendous changes on banking services and many bank customers are able to do their daily banking activities using recent advances of technology such as internet banking, telephone banking, etc. In this paper, we present an empirical investigation on the effects of strategic positioning for development of modern banking services. The proposed study designs a questionnaire in Likert scale and distributes it among some 385 randomly selected people who live in Tehran in 2013. The questionnaire consists of seven factors including property positioning, advantage positioning, consumer positioning, user positioning, competitive advantage positioning, quality positioning and merchandise category positioning. Using Spearman correlation as well as stepwise regression technique, the study has determined positive and meaningful relationships between different components of strategy positioning development of modern banking services.